(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
In the socio-economic reforms implemented in our country, it is important to effectively manage the personnel of industrial enterprises and to study the factors affecting it. Developing an effective personnel management mechanism, studying the factors affecting it, diversifying the economy, modernizing and technically updating the leading sectors of the industrial sector, especially in the context of a pandemic, all-round support for personnel management is defined as one of the main tasks implemented in the republic. This article analyzes the essence of personnel management and the main directions of its improvement.